1989
DOI: 10.1128/jcm.27.9.2019-2024.1989
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of epidemiological marker methods for identification of Salmonella typhimurium isolates from an outbreak caused by contaminated chocolate

Abstract: Plasmid profile analysis, restriction endonuclease analysis, and multilocus enzyme electrophoresis were used in conjunction with serotyping, bacteriophage typing, and biochemical fingerprinting to trace epidemiologically related isolates of Salmonella typhimurium from an outbreak caused by contaminated chocolate products in Norway and Finland. To evaluate the efficiency of the epidemiological marker methods, isolates from the outbreak were compared with five groups of control isolates not known to be associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…To investigate whether strains isolated from different stages of animal production can be connected with and reisolated from cases of human salmonellosis, typing methods other than traditional biochemical tests, serotyping, and patterns of susceptibility to antimicrobial agents may offer considerable assistance (18). Plasmid profiles have previously been used to link cases of disease with the source of infection (9,12), and this is considered to be a rapid, inexpensive and reproducible epidemiological typing system, applicable to a variety of bacterial pathogens (1 8). After initial isolation from broiler parent stock, S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether strains isolated from different stages of animal production can be connected with and reisolated from cases of human salmonellosis, typing methods other than traditional biochemical tests, serotyping, and patterns of susceptibility to antimicrobial agents may offer considerable assistance (18). Plasmid profiles have previously been used to link cases of disease with the source of infection (9,12), and this is considered to be a rapid, inexpensive and reproducible epidemiological typing system, applicable to a variety of bacterial pathogens (1 8). After initial isolation from broiler parent stock, S .…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid screening has been used to distinguish between different clones of a serovar of S. enterica in common source infections in animals (12) and in humans (9). The aim of the present study was to investigate the presence of plasmids in S. berta isolated from Danish broilers.…”
mentioning
confidence: 99%
“…Typhimurium (1986; Norway and Finland), Salm. Oranienburg* (2001;Germany) and Salmonella serotype Montevideo (2006; UK) (Craven et al 1975;D'Aoust et al 1975;Gill et al 1983;Greenwood and Hooper 1983;Hockin et al 1989;Kapperud et al 1989Kapperud et al , 1990Werber et al 2005;CDR-HPA 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Threlfall et al (21) reported that 92% of S. Enteritidis strains received by the Public Health Laboratory Service in England and Wales between 1981 and 1986 belonged to one of four PTs, PT4, 8, 6 and 11, with 85% of strains belonging to PT4, while studies in North Amer-ica show that the dominant phage types are PT8 and PT13a (1 1, 16). Plasmid profile analysis has been used to great effect as an epidemiological tool in outbreaks of salmonellosis (3,10,20,23). Whilst Threlfall et al (21) concluded that plasmid profile analysis of S. Enteritidis was not as sensitive as phage typing because of the low diversity of plasmid profiles observed among 534 strains, they nevertheless regarded plasmid profiling as an effective procedure for use in addition to phage typing for the subdivision of S. Enteritidis.…”
mentioning
confidence: 99%